Analysis of Product Development of Mango Fruit Juice Drink Using QFD (Quality Function Deployment) Method in Msme "So Food Drink" Kendari City - Awaliyah, Sitti Hajjah; Sarinah, Sarinah; Sakir, Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This research aims to analyze the development of mango fruit juice products using the Quality Function Deployment (QFD) method. Determining the research location was carried out purposefully. Data was collected using observation, questionnaires, interviews, and documentation methods. The analysis method used is Quality Function Deployment (QFD). The results of the research show that in the process of developing the mango fruit juice drink product brand "So Food Drink" using the QFD method, it was found that the priorities for development were in accordance with the desires and needs of consumers, respectively, including: ((1) Listed expiry date (11.20% ), (2) Product durability at room temperature (10.07%), (3) Attractive packaging design (8.89%), (4) Ease of obtaining mango fruit juice drink products (8.44%), ( 5 Does not use dangerous ingredients (7.96%), (6) Unchanged taste (7.85%), (7) Sweet taste (7.85%), (8) Has a long shelf life in the refrigerator (7.79%), (9) Thick texture (7.70%), (10) Has a brand label (7.58%), (11) Economical packaging (7.49%), and (12) Does not there is a sour taste (7.19%). The technical requirements or technical response of the "So Food Drink" brand mango fruit juice drink product to fulfill consumer desires and needs start with (1) sorting the mango fruit, (2) mixing or crushing the fruit, (3) packaging or labeling, (4) shelf life or temperature, and (5) marketing or promotion.